Prognostic Value of Strain by Tissue Tracking Cardiac Magnetic Resonance in Myocardial Infarction With Nonobstructive Coronary Arteries - Lei Chen; Bowen Qiu; Fuad A. Abdu; Lu Liu; Wen Zhang; Chunyue Wang; Jiasuer Alifu; Penglong Qi; Wenliang Che; Yuan Lu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Strain assessed by cardiac magnetic resonance (CMR) is a key prognostic indicator in myocardial infarction. However, the strain characteristics and prognostic value in myocardial infarction with nonobstructive coronary arteries (MINOCA) with different causes are unclear. This study aims to describe left atrial (LA) and left ventricular strain in patients with MINOCA and evaluate their predictive value for major adverse cardiovascular events (MACEs) in “true MINOCA” cases. Methods and Results This single‐center retrospective study included patients suspected of myocardial infarction who completed CMR during hospitalization. CMR images were used to obtain LA and left ventricular strain via CMR feature tracking. True MINOCA was defined by evidence of ischemia or infarction on CMR. MACEs included all‐cause death, recurrent myocardial infarction, stroke, heart failure, atrial fibrillation, and angina pectoris. This study included 386 patients, with a median time from admission to CMR of 4 days. LA and left ventricular strains varied by pathogenesis, with the lowest strain in patients with cardiomyopathy. For patients with true MINOCA, Cox regression showed that global longitudinal strain (hazard ratio [HR], 0.90 [95% CI, 0.82–0.99]; P=0.022) and LA reservoir strain (HR, 0.95 [95% CI, 0.91–0.99]; P=0.014) were independently associated with MACEs. Kaplan–Meier analysis indicated that patients with LA reservoir strain ≤21.25% or global longitudinal strain ≤16.4% had a significantly higher MACE risk (P<0.001). Integrating global longitudinal strain and LA reservoir strain improved MACE prediction. Conclusions LA and left ventricular strains vary among MINOCA pathogeneses. In true MINOCA patients, global longitudinal strain and LA reservoir strains independently predict MACE risk. Integrating these strains enhances MACE prediction. Registration URL: https://www.clinicaltrials.gov; Unique Identifier: NCT06502899.